Prekonomian Islam Pada Masa Peradaban Rasulullah SAW - Sovi Ani; Nurul Rizkia Hasibuan; Ananda Zulmi; M. Ardiansyah; Novan Wicaksana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this article is to understand the thinking of an Islamic economic system based on Islamic values ​​based on the Holy Koran and Hadith. The aim of implementing sharia economics is to create a civil society. The Prophet Muhammad made the economic system an example for all mankind in various fields of life to bring goodness to all mankind. Before the Islamic era, the Prophet Muhammad SAW served as a leader and messenger of Allah who changed the country's economic and financial system based on the Koran and Hadith. Apart from that, the Prophet Muhammad SAW was the first implementer of Islamic economic policy.